Perspectives on “Disease” and “Disability” in Child Health: The Case of Childhood Neurodisability - Miller, Anton Rodney; Rosenbaum, Peter (Frontiers in Public Health, 2016)
Chronic health conditions are often associated with what is termed disability. Traditional thinking has focused on diagnosis and treatment of chronic diseases and disorders, with less attention to people’s functional abilities and their contextual determinants. Understanding all of these factors is integral to addressing the predicaments and needs of persons with chronic conditions. However, these complementary yet distinct ‘worldviews’ reflected in what we call disease and disability perspectives often remain, at best, only vaguely articulated. In this paper, we explore and expand on these perspectives in light of conceptual advances, specifically the framework of WHO’s International Classification of Functioning, Disability and Health (ICF), and their epistemic underpinnings with reference to Wilhelm Windelband’s notions of nomothetic and idiographic types of knowledge. Our primary focus is children with neurodisability – life-long conditions that onset early in life and have functional consequences that impact developmental trajectories. We critically review and analyze conceptual material, along with clinical and research evidence relevant to the experiential and clinical realities of this population, to demonstrate the limitations of a biomedically-based diagnostic-therapeutic paradigm at the expense of a developmental and disability-oriented perspective. Our main aim in this paper is to argue for an explicit recognition of both disease and disability perspectives, and a more balanced and appropriate deployment of these concepts across the continuum of clinical services, research, policy-making and professional and public education in relation to children with neurodisability; we also provide concrete recommendations to advance this progressive strategy. The relevance of these aims and strategies, however, extends beyond this particular population.